PENGARUH KEPEMILIKAN INSTITUSIONAL, KOMITE AUDIT, KOMISARIS INDEPENDEN, DAN INDEPENDENSI AUDITOR EKSTERNAL TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Sub Sektor Property & Real Estate yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2018) - Gisela, Anyestika; Rita, Anugerah; Devi, Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research analyzed the effect of institutional ownership, audit committe, independent commissioners and independency of external auditor on financial statement integrity. The population in this study is all Sub Sector Property & Real Estate Companies listed in Indonesia Stock Exchange Period of 2015-2018. Sampling was done by using purposive sampling method using 40 companies. This study use data panel regression analysis by using Eviews Version 10 as statistical program used. The results of this study show that Institutional Ownership, Audit Committe, Independent Commissioners and Independency of External Auditor has effect on Financial Statement Integrity. Institutional Ownership, Audit Committe has significant value 0,0073 and 0,0023. and Independent Commissioners and Independency of External Auditor has significant value 0,004 and 0,027.Keywords: Financial Statement Integrity, Institutional Ownership, Audit Committee, Independent Commissioners and Independency of External Auditor